Epidural Analgesia in Labour: An Audit - Minahil Zaman,; Ali Salman,; Muhammad Usman Khan,; Amen Mansoor,; Shahryar,; Waleed Noor, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Labour epidural analgesia is a widely used pain relief method; however, challenges such as obesity, poor spinal anatomy, and uterine contractions can affect its success. Human factors, including communication errors and inadequate training, may also contribute to failure rates. This audit evaluates the factors influencing epidural placement success, patient satisfaction, and the role of ultrasound guidance in difficult cases. Methods: After obtaining ethical committee approval, a retrospective audit was conducted on epidural records from October 2023 to September 2024. A total of 317 pregnant women in labour who requested epidural analgesia were included. Consecutive (Non-Probability sampling technique) was used. Demographic data, parity, cervical dilation at the time of epidural placement, complications, anesthetist experience level, and patient satisfaction were recorded. Epidurals were administered by senior doctors (75%) and consultants (25%) using an 18G Tuohy needle in the sitting or lateral position. Difficult epidural placement was defined as requiring >2 intervertebral space attempts or >4 needle redirections. Statistical analysis was performed using SPSS v26.0, with p < 0.05 considered significant. Results: A total of 317 pregnant women in labor were included in the audit. Epidural administration varied significantly across months (p = 0.012), with the highest numbers in October 2023 (40) and the lowest in September 2024 (15). The mean patient age was 28.52 years, with most between 23 and 34 years. Younger patients reported slightly higher satisfaction (β = -0.08, p = 0.041). The most common cervical dilation at epidural administration was 3 cm (82 patients), followed by 4 cm (69 patients). Satisfaction levels varied significantly with cervical dilation (p = 0.007). Epidurals were administered by senior consultants (75%) or consultants (25%), with senior consultant-administered epidurals showing slightly higher satisfaction rates (66% "Excellent" vs. 60%, p = 0.054). Epidurals at L4-L5 had the highest satisfaction (p = 0.021). Patients receiving infusions reported lower satisfaction (β = -0.12, p = 0.032). Parity influenced satisfaction, with second-time pregnancies reporting the highest satisfaction (67% "Excellent") and fourth-time pregnancies the lowest (p = 0.019). Conclusion: Labour epidural placement is influenced by patient anatomy, cooperation, and provider expertise. Pre-labour anesthetic assessment and ultrasound guidance can improve success rates, while effective communication and standardized protocols enhance patient satisfaction.